2018
DOI: 10.3126/aej.v18i0.19895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation and potash levels on growth and yield of potato

Abstract: The experiment comprising four levels of irrigation (25, 30, 35 and 40 mm CPE) and four levels of potash (0, 100, 125 and 150 kg/ha) was conducted in Haryana Agricultural University, Hisar during winter season of 2010-11 and 2011-12 to find out the optimum level of irrigation and potash for better growth and yield of potato. The potato variety used for the investigation was Kufri Bahar. The treatments were laid out in a split plot design with three replications keeping a net plot size of 3.6x3.6 m. The plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
2
1
Order By: Relevance
“…The irrigation level of S100 resulted in a higher stem number per plant in 2021, while the irrigation level of S66 resulted in the highest number of stems per plant in 2022. Contrary to our research, Adhikari and Rana 29 and Kumar et al 23 showed that the effect of various irrigation levels on the number of stems per hill was not significant. Factors such as the storage conditions of tubers, the number of viable sprouts during planting, sprout damage and growing conditions during planting, physiological age of the seed tuber and tuber size also affect the number of stems 30 .…”
Section: Resultscontrasting
confidence: 99%
“…The irrigation level of S100 resulted in a higher stem number per plant in 2021, while the irrigation level of S66 resulted in the highest number of stems per plant in 2022. Contrary to our research, Adhikari and Rana 29 and Kumar et al 23 showed that the effect of various irrigation levels on the number of stems per hill was not significant. Factors such as the storage conditions of tubers, the number of viable sprouts during planting, sprout damage and growing conditions during planting, physiological age of the seed tuber and tuber size also affect the number of stems 30 .…”
Section: Resultscontrasting
confidence: 99%
“…This result agrees with (Ayas, 2010; Alva et al, 2012;Ayas, 2013;Gültekin and Ertek, 2018;Abdulrahman et al, 2018;Essah et al, 2020). Similar results were obtained in previous fertigation studies on potato (Ayas, 2013;Bero et al, 2014;Adhikari and Rana, 2017;Gültekin and Ertek, 2018;Essah et al, 2020). As the irrigation water amounts decreased, the yield decreased significantly as well.…”
Section: Discussionsupporting
confidence: 90%
“…Interaction of biochar and irrigations on growth and yield of crops is inadequately studied. However, irrigation and potassium interactions were studied in which differences were observed for the interactions of irrigation levels and potassium levels (Adhikari and Rana, 2018). In another study, conventional furrow irrigation was effective for growth and yield parameters of potato; indicating differences between irrigation methods (Verma et al, 2017).…”
Section: Interaction Effectmentioning
confidence: 99%